Age group differences in SFON tendency and arithmetical skills of four to seven year olds in four countries with different school starting ages - Hannula-Sormunen Minna; Batchelor Sophie; Torbeyns Joke; Simms Victoria; Nanu Cristina; Laakkonen Eero; De Smedt Bert (Elsevier, 2025)
This study investigated age group differences in Spontaneous Focusing on Numerosity (SFON) tendency and arithmetical skills across age groups with differing starting ages of formal mathematics instruction. Children (N = 685) aged 4–7 years participated from four countries, i.e., Northern Ireland, England, Belgium and Finland, where children start formal school at 4, 5, 6, and 7 years respectively. Children completed measures of SFON tendency, Arabic number naming, verbal arithmetic and written arithmetic. Results revealed strong age group effects for all measures and some developmental differences between SFON tendency and arithmetical skills. Whether children were, or were not, in school had a strong effect on SFON tendency but not on arithmetical skills. In the 5 and 6 years old age group, children already in school had significantly lower SFON tendency compared to those not yet in school. Within each country, when comparing consecutive age groups situated near school starting age, SFON tendency scores were similar in three out of the four countries. Results suggest both informal and formal mathematical skills need to be considered when assessing young children’s mathematical competence.